Narrating the Law: Possibilities, Pitfalls and Prospects - Wolff, Leon (Advances in Social Sciences Research Journal, 2014)
This article explores the possibilities and limits of using narrative analysis as a socio-legal method to illuminate issues of law and justice. It defines narrative analysis, explores the different ways the method has been used in the social sciences, and critically evaluates its use in interdisciplinary research on sexual harassment.